Allergy and Immunotoxicology in Occupational Health - Otsuki, Takemi; Petrarca, Claudia; Di Gioacchino, Mario; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2017)
This book offers a collection of the latest clinical and research findings related to allergies, one of the most frequently treated conditions in occupational medicine. The chapters not only cover asthma but also elaborate on contact dermatitis, rhinitis, and other allergic conditions, providing readers with a comprehensive overview of the substances disrupting autoimmunity and their effects on the human body. Allergy and Immunotoxicology in Occupational Health is a valuable resource for professionals and researchers in the occupational health sector, who will discover novel insights into immune effects, providing a foundation for future considerations of the health impairments caused by environmental and occupational exposure to these substances.
Chapter 1: Suppressive effects of asbestos exposure on the human immune surveillance system -- Chapter 2: Silica-induced immunotoxicity: chronic and aberrant activation of immune cells -- Chapter 3: Engineered nano materials and allergy -- Chapter 4: Allergens in Occupational Allergy: Prevention and Management. Focus on Asthma -- Chapter 5: Particulate-driven type-2 immunity and allergic responses -- Chapter 6: Traditional and Emerging Occupational Asthma$1!#((BOA$1!#)(Bin Japan -- Chapter7: Skin sensitization model based on only animal data by qualitative structure-toxicity relationships (QSTR) approach -- Chapter 8: Non-industrial indoor environments and work-related asthma, a review -- Chapter 9: Combined effect on Immune and Nervous System of Aluminum Nanoparticles -- Chapter 10: Non Pulmorary Effects of Isocianates -- Chapter 11: Skin Exposure to Nanoparticles. ><.s
Keywords: Medicine; Immunology; Pharmacology; Allergy; Public health; Medicine & Public Health; Public health; Immunology; Pharmacology/Toxicology.; Allergology